Characterization of aerosol optical properties and their seasonal dynamics over Pokhara Valley, Central Nepal - Kuikel, Shyam; Pandey, Santosh (Himalayan Physics, 2026)
Understanding the variation of aerosol optical properties is crucial for assessing air quality and climate impacts in mountainous regions such as Pokhara Valley, Nepal. This study investigates the monthly, seasonal, and wavelength-dependent behavior of aerosols over Pokhara during 2020-2022 using high-quality Level 2.0 AERONET data. Aerosol Optical Depth (AOD) at five wavelengths (440-1020 nm), together with the Angstrom exponent (α) and turbidity coefficient (β), was analyzed to characterize particle size and atmospheric loading. The results reveal pronounced seasonal variability, with the highest AOD during the pre-monsoon season (0.99 ± 0.12 at 440 nm in April) and the lowest during the monsoon (0.20 ± 0.05 at 1020 nm in August). A clear wavelength dependence is observed, with higher AOD at shorter wavelengths and lower values at longer wavelengths, indicating dominance of fine-mode aerosols. This seasonal contrast is governed by enhanced dust transport and biomass burning during the dry pre-monsoon months, while monsoonal precipitation efficiently scavenges aerosols. An inverse relationship between beta and visibility demonstrates that increased aerosol loading degrades atmospheric clarity. Overall, the findings highlight the combined influence of seasonal meteorology, emission sources, precipitation-driven removal, and spectral aerosol behavior on air quality over Pokhara Valley, providing valuable insights for regional air-quality management, aerosol-climate studies, and health-protection strategies in Nepal’s rapidly urbanizing mountainous environments.